Tarlov cyst- a rare occurrence: a short series of two cases - Arora, Kamal Kumar; Chaudhary, Priti (International Journal of Research in Orthopaedics, 2020)
Tarlov cysts were first noted and described by Tarlov in 1938. The overall incidence of these is somewhere between 08%-09% of the total population with female preponderance. Most commonly, they are in sacral region. Patients were either asymptomatic or reported in the OPD with low backache with radiculopathy CT guided micro fenestration of the cyst was done using the aspiration-injection technique in the symptomatic patient. The primary outcomes, pain and function, were assessed by using the lumbar spine outcomes questionnaire. The outcome in our cases was excellent in terms of pain intensity, personal care, lifting, walking, sitting etc., requiring no further surgical intervention.